Learning how to prepare athletes for peak performance: Use of mental imagery training as a psychological strategy to enhancing motor learning, retention and transfer of sport rifle marksmanship - Taktek, K.; Zinsser, N.; Fielitz, L.; Corbari, G.; Miller, S.; St. John, R. (Journal of Sport and Human Performance, 2019)
This article is intended to (a) compare the effects of mental imagery and physical practice only on the learning and transfer of an open motor skill; (b) identify the mental imagery modality (visual, kinesthetic, or temporal) which is most efficient for sport rifle marksmanship; and (c) determine the relationship between movement image vividness and motor performance. Seventy students from the United States Military Academy, West Point, New York, participated in this study. They used their dominant hand to shoot (live-fire shooting) rotating targets. This study comprised four principal phases, namely the pretest, treatment, posttest (retention) and transfer. The results demonstrated that the retention performance obtained by each group using mental imagery combined with physical practice was equivalent to that produced by physical practice only. Furthermore, each group using visual or kinesthetic mental imagery combined with physical practice showed significantly superior performance than physical practice only during the transfer. These results may be explained by three functional evidences, namely behavioural, central and peripheral (Feltz & Landers, 2007; Holmes & Collins, 2001).